Pharmacognostical Analysis and In Vitro Antioxidant Activity of Scoparia dulcis L - Sharma, Abhishek; Singh Saluja, Manmeet; Jain, Priya (Journal of Biomedical and Pharmaceutical Research, 2023)
Scoparia dulcis L. is widely used in the traditional system of medicine for treating liver ailments. In the present study the detailed pharmacognostical evaluation of Scoparia dulcis Linn. whole plant (Scrophulariaceae), including morphology, microscopy, physicochemical, phytochemical screening and in vitro antioxidant activity of 70% ethanol extract. Microscopy of different plant part was done by performing transverse sections and longitudinal sections, which were identified by the different staining reagents and dyes. Physicochemical constants were done for whole plant; it includes ash value, extractive value and moisture content. Phytochemical screening was done for aqueous and 70% ethanolic extract in maceration and soxhletion, results revealed the presence of alkaloids, glycosides, carbohydrates, phenolic compound, flavonoids, saponins, proteins, and amino acids. Ethanolic extract were tested for their in vitro 1, 1- Diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity. These study includes parameters to establish the authenticity of S. dulcis and can possibly help to differentiate the drug from its other species and this may be attributed to its free radical scavenging potential, which in turn may be attributed to the presence of 2o metabolites.